1998
DOI: 10.1086/306381
|View full text |Cite
|
Sign up to set email alerts
|

TheCOBEDiffuse Infrared Background Experiment Search for the Cosmic Infrared Background. III. Separation of Galactic Emission from the Infrared Sky Brightness

Abstract: The Cosmic Infrared Background (CIB) is hidden behind veils of foreground emission from our own solar system and Galaxy. This paper describes procedures for removing the Galactic IR emission from the 1.25 -240 µm COBE DIRBE maps as steps toward the ultimate goal of detecting the CIB. The Galactic emission models are carefully chosen and constructed so that the isotropic CIB is completely retained in the residual sky maps. We start with DIRBE data from which the scattered light and thermal emission of the inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
221
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(243 citation statements)
references
References 76 publications
21
221
0
1
Order By: Relevance
“…For comparison, the "reference value" commonly adopted for the I 60 µm /I 100 µm ratio in high-latitude cirrus is ∼0.2 (see e.g. Arendt et al 1998). M 81 presents a high color (I 60 µm /I 100 µm ∼ 0.3) compared to Galactic cirrus of the same brightness, although it is not very different from diffuse cirrus colors or from that of the loop itself.…”
Section: Far-infrared Emissionmentioning
confidence: 99%
“…For comparison, the "reference value" commonly adopted for the I 60 µm /I 100 µm ratio in high-latitude cirrus is ∼0.2 (see e.g. Arendt et al 1998). M 81 presents a high color (I 60 µm /I 100 µm ∼ 0.3) compared to Galactic cirrus of the same brightness, although it is not very different from diffuse cirrus colors or from that of the loop itself.…”
Section: Far-infrared Emissionmentioning
confidence: 99%
“…Gordon 1995;Wu et al 2007) to the more quiescent diffuse media Arendt et al 1998). Many processes linked to star formation such as stellar winds (Hoefner 2009), supernovae shocks, photodestruction by high-mass stars etc.…”
Section: Introductionmentioning
confidence: 99%
“…For higher column densities the dust emission systematically exceeds that expected by extrapolating the correlation. Examining specific high Galactic latitude regions, Arendt et al (1998) and Reach et al (1998) found infrared excesses with respect to N HI , with a threshold varying from 1.5 to 5.0 × 10 20 cm −2 .…”
Section: Modelmentioning
confidence: 99%
“…Many studies, mostly using the IRAS and COBE data compared with various 21-cm surveys (Boulanger & Pérault 1988;Joncas et al 1992;Jones et al 1995;Boulanger et al 1996;Arendt et al 1998;Reach et al 1998;Lockman & Condon 2005;MivilleDeschênes et al 2005), have revealed the strong correlation between far-infrared/submm dust emission and 21-cm integrated emission W HI 3 at high Galactic latitudes. In particular Boulanger et al (1996) studied this relation over the whole high Galactic latitude sky.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation